A phase I and pharmacokinetic study of 12-h infusion of flavone acetic acid - Olver, I N; Webster, L K; Bishop, J F; Stokes, K H (Cancer chemotherapy and pharmacology, 1992)
This phase I study investigated flavone acetic acid (FAA) given as a 12-h intravenous infusion every 3 weeks in the absence of urinary alkalinisation. Cohorts of three patients were treated at doses of 7, 10 and 13 g/m2. One subject had colon cancer; 5, renal cancer; and 3, lung cancer. The Eastern Cooperative Oncology Group (ECOG) performance status was 0 in four patients, 1 in two subjects and 2 in three cases. The maximum tolerated dose was 13 g/m2. The dose-limiting toxicities were WHO grade 3 hypotension and grade 3 diarrhoea. Other toxicities included lethargy and dizziness, nausea, temperature fluctuation, myalgia and dry mouth, but no significant myelosuppression was encountered. One patient receiving 10 g/m2 for renal cancer showed a partial response that lasted for 3 months and included the resolution of pulmonary and cutaneous metastases. The pharmacokinetics showed large interpatient variability. At 12-16 h post-infusion, the plasma elimination profile entered a plateau phase, with frequent increases in concentration suggesting enterohepatic recycling. Neither peak FAA levels nor AUC values were dose-dependent at the doses studied. Peak plasma levels were 101-402 micrograms/ml and AUC (0-48 h) values were 75-470 mg ml-1 min. Plasma protein binding varied with total concentration. Two metabolites were detected in the plasma, and both also underwent apparent enterohepatic recycling. Repeat dosing resulted in decreases of up to 48% in peak levels and AUC values for FAA in three of six patients. Of the total FAA dose, 39%-77% was excreted in the urine as FAA or metabolites within 2 days. The dose recommended for further phase II studies is 10 g/m2.